A Small Macro Econometrıc Model of Azerbaıjan Economy - VALIYEV, Vilayat; SULEYMANOV, Arzu; NAMAZOVA, Natavan (Journal of Ecohumanism, 2024)
In the presented article, the construction of the Macroeconometric model for short- and medium-term forecasting of indicators of socio-economic development in the economy of Azerbaijan has been carried out. The model consists of 64 variables (41 endogenous, 23 exogenous) and 41 equations, built in four blocks (national income account, deflators, balance of payments and public finance). The database of the model is formed in four parts, covering the years 1995-2017 on an annual basis, including national income account, deflators, balance of payments and public finance. The development of the database was carried out together with the State Statistical Committee of the Republic of Azerbaijan (SSC) in full compliance with UN standards. The methodology used includes time series stationarity tests, ARIMA models, vector error correction models and other econometric methods. As a result, a compact macroeconometric model for the economy of Azerbaijan was established. Based on the model, predictions were processed in the short-term scientific research approach and compared with the actual results.